Differential Cortical Thickness across the Central Sulcus: A Method for Identifying the Central Sulcus in the Presence of Mass Effect and Vasogenic Edema - Biega, T.J.; Lonser, R.R.; Butman, J.A. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Identification of the motor strip on MR imaging studies is difficult in the presence of mass effect and vasogenic edema because sulcal landmarks are obscured. We hypothesize that a difference in cortical thickness between the motor and sensory strips is readily apparent on T2-weighted images in the presence of vasogenic edema and reliably identifies the central sulcus.METHODS: Thirteen patients with brain tumors resulting in vasogenic edema near the central sulcus were identified. The cortical thickness of the anterior and posterior banks of the central sulcus as well as the neighboring sulci in the frontal and parietal lobes were measured from T2-weighted images. Similar measures were obtained from neighboring sulci in the frontal and parietal lobes. Location of the central sulcus was confirmed with standard anatomic landmarks in all patients and by intraoperative cortical mapping in 2 patients.RESULTS: A twofold difference in cortical thickness between the anterior and posterior banks of the central sulcus uniquely identified the central sulcus on T2-weighted images in the presence of vasogenic edema, despite the marked distortion of sulcal anatomy as a result of mass effect. This relationship was not present in neighboring sulci.CONCLUSION: Cytoarchitectonic differences in the motor and sensory cortices result in a markedly thicker posterior than anterior bank of the central sulcus that is readily visible on routine T2-weighted images in the presence of vasogenic edema. Therefore, the cortical thickness can serve as a complementary method in identification of the motor strip in patients with mass effect.